Revealing the effect of N-content in Fe doped graphene on its catalytic performance for direct oxidation of methane to methanol - Thantip Roongcharoen (2020)
© 2020 Elsevier B.V. The effect of N-content in Fe doped divacancy graphenes (Fe-NxG, x = 0–4) on its catalytic performance for oxidation of methane to methanol by N2O was investigated by PBE-D3 method. The formation of Fe-NxG surfaces with N-content ranging from 2 to 4 is predicted to be spontaneous, and Fe is strongly trapped into the surfaces without clustering. The overall reaction proceeds in two consecutive steps; 1) the N2O dissociation on Fe active site yielding a FeO and 2) the methane oxidation with FeO to methanol. Both Fe and FeO active centers hold strong magnetic moments and intrinsically drive the reactions through the radical mechanism and the methane activation is the rate-determining step. The results reveal that Fe-N3G shows the highest catalytic performance. The difference in catalytic activity originates from the distinct electronic structure and magnetic moment of the catalytic systems. Interestingly, the density of states of the Fe and FeO near the Fermi level of the catalysts is a key factor that regulates the catalytic activity for N2O dissociation and methane conversion to methanol, respectively. Our results provide an understanding of the reaction mechanisms controlled by magnetic and electronic properties of the catalysts which can be manipulated by N-content in the systems.